The Effects of Essay Tests and Learning Methods on Students’ Chemistry Learning Outcomes - RISNITA, Risnita; BASHORI, Bashori (Journal of Turkish Science Education, 2020)
This study aims to test the effects of essay tests and learning methods on students’ chemistry learning outcomes. The sample of this study was drawn from grade 11 students at Jambi State Senior High Schools through a multi-stage random sampling technique. Within a factorial experimental design, the data were analyzed using the covariance analysis technique (ANCOVA) with Tukey's test. The experimental procedure was carried out using the requirement tests (e.g., normality and homogeneity). The results showed that Chemistry learning outcomes of the students, who were exposed to the use of higher contextual learning methods, were better than the control group, who were instructed with conventional learning methods. Also, the present study pointed to an interaction between the effects of formative tests and learning methods on chemistry learning outcomes when the influences of early skills were controlled. In light of these findings, the present study suggests that teachers use related teaching methods and essay tests to empower their students ‘learning processes.